Performance of Maize and French Bean Cultivated Under Intercropping System - Rahman, Md Rashedur; Shabrin, Eshrat; Tandra, Joysree Pual; Usha, Shagufa Akter; Bhuiya, Md. Sultan Uddin (Fundamental and Applied Agriculture, 2025)
In order to investigate the yield benefits and financial gains associated with the variable row arrangements of French bean intercropped with the base crop maize, an experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during rabi season between October to April 2019. The research comprised eight treatments: i) Sole maize, ii) Sole French bean, iii) one row of maize followed by two rows of French bean intercropping, iv) one row of maize followed by three rows of French bean intercropping, v) one row of maize followed by four rows of French bean intercropping, vi) two rows of maize followed by two rows of French bean intercropping, vii) two rows of maize followed by three rows of French bean intercropping and viii) two rows of maize followed by four rows of French bean intercropping. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications and total plots number were 24. The results show that the systems of intercropping maize and French bean had a substantial impact on the maize productivity. The highest seed yield was obtained from sole maize (8.56 t ha-1). In intercropping situation, the highest seed yield (5.66 t ha-1) was obtained from two rows of maize followed by four rows of French bean intercropping and the lowest seed yield (3.64 t ha-1) was obtained from one row of maize followed by two rows of French bean intercropping. Single maize had the highest maize equivalent yield (8560 kg ha-1). The maximum Land Equivalent Ratio was obtained from one row of maize interplanted with four rows of French bean. Economic analysis revealed that two rows of maize followed by four rows of French bean intercropping had the highest gross return (202160 Tk ha-1), the highest net return (96759 Tk ha-1), and the highest Benefit-Cost Ratio (1.92). Thus, according to the current analysis, the most advantageous intercropping strategy in terms of yield and financial gain is to plant two rows of maize with four rows of French bean. Maize, French bean, Productivity, Profitability,Land Equivalent Ratio, Benefit-Cost Ratio